One welfare : a framework to improve animal welfare and human well-being - Pinillos, Rebeca Garcia (CABI, 2018)
This book focuses on the definitions, concepts, frameworks and guidelines of One Welfare. The book is divided into five sections (section 1, the connections between animal and human abuse and neglect; section 2, the social implications of improved animal welfare; section 3, animal health and welfare, human well-being, food security and sustainability; section 4, assisted interventions involving animals, humans and the environment; and section 5, sustainability (connections between biodiversity, the environment, animal welfare and human well-being)) with tables, case studies and review